PERENCANAAN STRUKTUR ATAS GEDUNG PASAR SURANTIH KABUPATEN PESISIR SELATAN - Muhammad Arif Hanafia; Deddy Kurniawan; Febrimen Harista (Ensiklopedia Research and Community Service Review, 2022)
Surantih Market is one of the trade locations on a large scale, this market is a central trading center in the South Coast which has great potential in increasing the economy, especially the local community. So that the Surantih market plays an important role in improving the economy. To realize these things, it requires physical facilities and facilities such as access to traffic, offices and market buildings. The goal that the writer wants to achieve in this thesis is the planning of the Pasar Surantih building with the ductile principle in order to create a building that is safe and resistant to earthquakes. This is one of the bases for planners to plan the Pasar Surantih building. . The results obtained that the material used is steel fy = 420 Mpa and concrete quality fc' = K-300 (24.9 Mpa). For floor slab reinforcement, reinforcement is used for the x = 10 – 150 direction, while the y direction = 10 – 150. Column planning uses steel fy = 420 Mpa and concrete quality fc' = 24.9 MPa with a column size of 1 55 cm x 55 cm, for column 2 50cm x 50cm, and for column 3 40cm x 40cm. While the design of the beam using steel quality fy = 300 Mpa and concrete quality fc' = K-300 (24.9 Mpa) Mpa with sizes for the main beam 70cm x 45cm, child beam 50cm x 30cm.Keywords : Upper Structure, Multi-storey Building, Moment, Shear Force